2005
DOI: 10.1111/j.1742-7843.2005.pto960402.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transcription of Contractile 5‐Hydroxytryptamine 2A Receptors via Extracellular Signal‐Regulated Kinase 1/2 after Organ Culture of Rat Mesenteric Artery

Abstract: 5-Hydroxytryptamine (5-HT) has been found to elicit enhanced contractile effects in some vascular disorders. The present study was designed to examine if vascular 5-HT 2A receptors are up-regulated during organ culture and if the extracellular signal-regulated protein kinase 1/2 (ERK1/2) pathways are involved. Compared with fresh rat mesenteric artery ring segments, the contractile responses to 5-HT were significantly increased in the segments cultured for 6, 24 or 48 hr (PϽ0.05, PϽ0.01, PϽ0.01, respectively).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…In the present study, we focused on the role of MAPK and intracellular calcium to understand the process of contraction induced via endothelin ET B receptors in rat mesenteric artery and demonstrated that activation of MAPK ERK1/2 is required for the contraction. This is supported by previous findings that contraction induced via G-protein-coupled receptors 5-HT 2A receptors in rat mesenteric artery requires ERK1/2 activities (Cao et al, 2005). Nifedipine, a selective calcium channel blocker markedly reduced sarafotoxin 6c-induced contraction.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, we focused on the role of MAPK and intracellular calcium to understand the process of contraction induced via endothelin ET B receptors in rat mesenteric artery and demonstrated that activation of MAPK ERK1/2 is required for the contraction. This is supported by previous findings that contraction induced via G-protein-coupled receptors 5-HT 2A receptors in rat mesenteric artery requires ERK1/2 activities (Cao et al, 2005). Nifedipine, a selective calcium channel blocker markedly reduced sarafotoxin 6c-induced contraction.…”
Section: Discussionsupporting
confidence: 76%
“…The mechanisms responsible for the upregulation of endothelin ET B receptors involves gene transcription and include activation of protein kinase and mitogen-activated protein kinase (MAPK) pathways consist of ERK1/2 (Uddman et al, 2003). It has been observed that of MAPK and down stream transcriptional factors regulate the gene expression of G-protein-coupled receptors, such as endothelin ET B , 5-hydroxytryptamine (5-HT) 2A and bradykinin B 1 and B 2 receptors in response to extracellular stimuli (Cao et al, 2005, Zhang et al, 2004and Zhang et al, 2005. Typically, these events induce a contractile phenotype (Moller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Organ culture has also been shown to enhance the contractile response to the selective ET B receptor agonist, sarafotoxin S6c, while having no effect on the prostaglandin F 2α and interleukin-1β contraction in the human temporal artery (White et al, 1999). Cao et al (2005) has also demonstrated an organ culture induced increase in the contractile response to 5-hydroxytryptamine in the rat mesenteric artery. Previously, using pigs 6-9 months old, we found a T max to 3 × 10 −7 M ET-1 of 121 ± 8% and 227 ± 20% of the maximum response to 80 mM KCl in fresh and organ cultured rings, respectively (Hill et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Pinacidil-induced relaxation responses in aortas and mesenteric arteries The responses of the arterial segments to pinacidil were measured with a myograph system [10,11] . Briefly, the fresh vessels were then cut into 1 or 2 mm-long cylindrical segments.…”
Section: Animals and Materialsmentioning
confidence: 99%